(3EOGQI GdeTQhYGJ GdUZjQI (B:s (3eONd HjFj ebGQf (B/s - (3YeQ, Cjef Ydjs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2007)
(3eaghe GdeTQhYGJ GdUZjQI,GdeYGjjQ GdSGFOI aj Jbjje GdeTQhYGJ,GdUfGYGJ GdJMhjdjI CSGS GdeTQhYGJ GdUZjQI hGdJMhdGJ GdEbJUGOjI GdgGFdI,bOQI GdUfGYGJ GdUZjQI Ydi GeJUGU aGFV GdYeGdI hGdeSGgeI GdEjLGHjI aj Md eTcdI GdHWGdI,CHQR GdeYhbGJ hGdeTcdGJ GdJj JhGLg GdeTQhYGJ GdUZjQI HGdJWHjb Ydi eUQ,JLGQH ebGQfI YQHjI hOhdjI ddeTQhYGJ GdUZjQI,ebJQMGJ HCSGdjH hhSGFd dJfejI bWGY GdeTQhYGJ GdUZjQIs
(3HHdjhZQGajG(B:(3U(B.367-372s
Keywords: (3GdeTQhYGJ(B-(3JfXje hEOGQIs